(untitled) - Mirsepassi, Ali (Cambridge, 2000)
In this thought-provoking book, Ali Mirsepassi explores the concept of modernity and exposes the Eurocentric prejudices underlying its development. He provides a new interpretation of Islamic Fundamentalism through a detailed analysis of the ideas of key Islamic intellectuals and argues that the Iranian Revolution was not a simple clash between modernity and tradition but an attempt to accommodate modernity within a sense of authentic Islamic identity and culture. He concludes by assessing the future of secularism and democracy in the Middle East in general, and in Iran in particular.
Keywords: Politics and culture,Islam and politics,Chính trị và văn hóa,Iran,Đạo Hồi và chính trị; Chính quyền và chính trị; Thế kỷ 20; Iran,Iran,Iran,Iran